Management of early blight of potato, Alternaria solani using fungicides and botanicals - Arunakumara et al, K T (Indian Journal of Plant Protection, 2018)
Among 10 fungicides, 10 botanicals and 6 bioagents evaluated under in vitro condition against Alternaria solani, 0.15% propiconazole 25EC, 0.3% ridomil MZ72WP, 0.3% copper oxychloride 50WP, 0.3% mancozeb75WP, Clerodendron inerme (10%), Eucalyptus globulus (10%), Eupatorium odoratum (10%) and Trichoderma harzianum gave the maximum inhibition of mycelial growth of A. solani. The feld evaluation of different fungicides and botanicals during Rabi 2013-14 indicated that 0.1% propiconazole 25EC showed the least Per cent disease index (28.2), followed by 0.2% pyraclostrobin 20WG (35.1PDI) and 0.1% azoxystrobin-23EC (42.1 PDI). However, maximum PDI was recorded from control plot (88.4). All fungicide sprayed treatments showed less tuber infection ranging from 1.1 to 5.0 per cent. Highest tuber yield (21.37 t/ha) was recorded from plots sprayed with 0.1% propiconazole 25EC and least tuber yield was recorded from control plot (16.68 t/ha). During Kharif 2014 as well, 0.1% propiconazole 25EC was signifcantly superior to other treatments and similar trend was observed for other treatments also.